Regenerate the monstrous. An essay (Itinera, 2023)
The article moves from the idea of monster as a “cultural predicate” referable to a wide linguistic and symbolic repertoire proper to the overall human history. In this perspective, particular attention is paid to the variegated viewpoints on monstrosity that, from the initial teratology of “natural” sign, develops into a teratology of a specifically “social” character. Hence the indication that, from a material standpoint, shows how the transformations of feeling, thinking, and acting related to nowadays work activities, make it possible to associate certain characteristics of monstrosity – clearly not conceivable only in negative terms – to new productive subjects and cooperating singularities.
Keywords: cultural predicate, social character, transformations, productive subjects, cooperating singularities.